Size and causes of the underground economy in Spain: A correction of the record and new evidence from the MCDR approach - Michael Pickhardt; Jordi Sardà (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2011)
We review existing estimates of the size of the Spanish underground economy, apply the Ahumada et al. (2007, RIW) correction procedure to some of them and calculate the size of the underground economy in Spain for the period 1960 through 2009 by using the modified-cash-deposits-ratio (MCDR) approach recently developed by Pickhardt and Sardà (2011, EJLE). We then extend the MCDR approach with respect to an analysis of the causes of the Spanish underground economy. Contrary to most other studies, we show that the latter is not predominantly caused by tax pressure, but by labor market aspects, macroeconomic influences and criminal activities. Based on these findings we derive some unprecedented policy recommendations.
Keywords: O17; H26; C22; 330; underground economy; shadow economy; hidden economy; black economy; cash-deposit-ratio; currency demand approach; MIMIC approach; Schattenwirtschaft; Geldumlauf; Geldnachfrage; Spanien